Relationship Between Arm Span Measurements And Body Height In Mojkovac - Marko Knezevic (Journal of Anthropology of Sport and Physical Education)
In light of rather sparse recent scientific literature, the purpose of this research study was to examine the body height in both sexes of Montenegrin adults nowadays. Furthermore, the relationship between arm span and body height, which varies in different ethnic and racial groups, was used as an alternative to estimating the body height for some groups of the population. The nature and scope of this study analyses 34 adolescents (14 men, aged 18.15±0.37 and 20 women, aged 18.00±0.00) from Mojkovac. The anthropometric measurements were taken according to the protocol of the International Society for the Advancement of Kinanthropometry (ISAK). Means and standard deviations were obtained. A comparison of means of body heights and arm spans within and between the sexes were carried out using a t-test. The relationships between body height and arm span were determined using simple correlation coefficients and their 95% confidence interval. A linear regression analysis was then performed to examine the extent to which arm span can reliably predict body height. The results have shown that male from Mojkovac are 183.82±6.87 centimetres tall and have an arm span of 186.80±7.43 centimetres, while female from Mojkovac are 167.75±4.96 centimetres tall and have an arm span of 167.17±4.46 centimetres. Comparing the results with other studies has shown that both sexes of Mojkovac are very tall.